AKURASI ARAH KIBLAT MASJID MUHAMMADIYAH DAN MASJID AS’ADIYAH DI KOTA SENGKANG - Yusfiar, Muh; Latuconsina, Mahyuddin (HISABUNA: Jurnal Ilmu Falak, 2020)
Facing the Qibla is an Islamic obligation, therefore everyone can at least know the procedures for determining the direction of Qibla so that when someone is on his way to a place, he is no longer confused as to where he should be facing when performing worship, especially prayer. In the city of Sengkang there are two Islamic organizations that are quite influential in matters of science related to Islam namely, Muhammadiyah and As’adiyah. Therefore in this paper, the authors conducted a study related to the direction of the two mosques in different organizations namely the Muhammadiyah Mosque and the As’adiyah Mosque, and the issues raised were related to the method used in determining the Qibla direction by the two organizations, and the accuracy of each the mosque will then be examined directly in the field in order to obtain complete and valid data. In determining the direction of the Qibla direction of the Muhammadiyah Mosque, there are a variety of methods used, and there are still many whose Qibla direction deviates from the existing Qibla direction. Whereas in determining the direction of the Qibla of the As’adiyah Mosque there are also various methods used and there is also an inclination towards several mosques but not far enough from the existing provisions. Thus, in determining the direction of the mosque’s qibla, it is better to have the involvement of an institution that oversees the issue such as the Ministry of Religion or to provide socialization to the community, mosque administrators, and religious leaders regarding the direction of good and correct qibla.